α-Synuclein Promotes Dilation of the Exocytotic Fusion Pore - Logan, Todd (Nat Neurosci, 2017)
The protein α-synuclein has a central role in the pathogenesis of Parkinson’s disease (PD). Similar to other proteins that accumulate in neurodegenerative disease, however, the function of α-synuclein remains unknown. Localization to the nerve terminal suggests a role in neurotransmitter release and over-expression inhibits regulated exocytosis, but previous work has failed to identify a clear physiological defect in mice lacking all three synuclein isoforms. Using adrenal chromaffin cells and neurons, we now find that both over-expressed and endogenous synuclein serve to accelerate the kinetics of individual exocytotic events, promoting cargo discharge and reducing pore closure (‘kiss-and-run’). Thus, synuclein exerts dose-dependent effects on dilation of the exocytotic fusion pore. Remarkably, mutations that cause PD abrogate this property of α-synuclein without impairing its ability to inhibit exocytosis when over-expressed, indicating a selective defect in normal function.